Comparing Methods of Assessing Dog Rabies Vaccination Coverage in Rural and Urban Communities in Tanzania - Sambo, Maganga; Johnson, Paul C. D.; Hotopp, Karen; Changalucha, Joel; Cleaveland, Sarah; Kazwala, Rudovick; Lembo, Tiziana; Lugelo, Ahmed; Lushasi, Kennedy; Maziku, Mathew; Mbunda, Eberhard; Mtema, Zacharia; et al. (Frontiers in Veterinary Science, 2017)
Rabies can be eliminated by achieving comprehensive coverage of 70% of domestic dogs during annual mass vaccination campaigns. Estimates of vaccination coverage are therefore required to evaluate and manage mass dog vaccination programmes, however there is no specific guidance for the most accurate and efficient methods for estimating coverage in different settings. Here we compare post-vaccination transects, school-based surveys and household surveys across 28 districts in southeast Tanzania and Pemba island covering rural, urban, coastal and inland settings, and a range of different livelihoods and religious backgrounds. These approaches were explored in detail in a single district in northwest Tanzania (Serengeti), where their performance was compared with a complete dog population census that also recorded dog vaccination status. Post-vaccination transects involved counting marked (vaccinated) and unmarked (unvaccinated) dogs immediately after campaigns in 2155 villages (24,721 dogs counted). School-based surveys were administered to 8,587 primary school pupils each representing a unique household, in 119 randomly selected schools approximately two months after campaigns. Household surveys were conducted in 160 randomly selected villages (4488 households) in July/August 2011. Costs to implement these coverage assessments were $12.01, $66.12 and $155.70 per village for post-vaccination transects, school-based and household surveys, respectively. Simulations were performed to assess the effect of sampling on the precision of coverage estimation. The sampling effort required to obtain reasonably precise estimates of coverage from household surveys is generally very high and probably prohibitively expensive for routine monitoring across large areas, particularly in communities with high human to dog ratios. School-based surveys partially overcame sampling constraints; however were also costly to obtain reasonably precise estimates of coverage. Post-vaccination transects provided precise and timely estimates of community-level coverage and that could be used to troubleshoot the performance of campaigns across large areas. However, transects typically over-estimated coverage by around 10% which therefore needs consideration when evaluating the impacts of campaigns. We discuss the advantages and disadvantages of these different methods, and make recommendations for how vaccination campaigns can be better monitored and managed at different stages of rabies control and elimination programmes.